2015
DOI: 10.1021/acs.nanolett.5b00680
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Tunable and Fully Biocompatible Silk Nanoplasmonic Optical Sensor

Abstract: Novel concepts for manipulating plasmonic resonances and the biocompatibility of plasmonic devices offer great potential in versatile applications involving real-time and in vivo monitoring of analytes with high sensitivity in biomedical and biological research. Here we report a biocompatible and highly tunable plasmonic bio/chemical sensor consisting of a natural silk protein and a gold nanostructure. Our silk plasmonic absorber sensor (SPAS) takes advantage of the strong local field enhancement in the metal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 31 publications
1
85
0
Order By: Relevance
“…However, for angle interrogation, only monochromatic light is required, it is possible to achieve higher signal-to-noise ratio due to the wavelength and power stability of the source. [5][6][7][8][9][10][11] Thus, angle interrogation is adopted in this article.…”
Section: Introductionmentioning
confidence: 99%
“…However, for angle interrogation, only monochromatic light is required, it is possible to achieve higher signal-to-noise ratio due to the wavelength and power stability of the source. [5][6][7][8][9][10][11] Thus, angle interrogation is adopted in this article.…”
Section: Introductionmentioning
confidence: 99%
“…7 Specifically, it has been greatly demonstrated that the metallic nanostructures with strongly enhanced local electric field bears the advantages of being non-destructive, highly-sensitive and label-free bio-sensor. [8][9][10] Of particular interest is the combination of metallic nanostrucrures and Raman spectroscopy that would provide a powerful analytical technique, namely, surface-enhanced Raman scattering (SERS) for the ultra-sensitive bio-chemical detection even to a single molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…These plasmonic structures can be used as sensors or to enhance fluorescence [120]. A spectral shift sensitivity up to 1200 nm/RIU has been demonstrated for sensing glucose [121]. …”
Section: Plasmonic Devicesmentioning
confidence: 99%